Neurofibromatosis type 1 (NF1): knowledge, experience, and reproductive decisions of affected patients and families. Issue 7 (July 1993) - Benjamin, C M; Colley, A; Donnai, D; Kingston, H; Harris, R; Kerzin-Storrar, L
Abstract : Eighty-one subjects (56 affected patients and 25 parents of isolated affected cases) from 63 families with neurofibromatosis type 1 (NF1) on the North Western Regional Genetic Family Register (NWRGFR) were interviewed. Patients were interviewed either before (n = 26) or after (n = 55) genetic counselling. In the group as a whole, knowledge of the clinical features and the genetic aspects of the condition was poor (mean score 7 within the range of 0 to 18). The following factors were significantly associated with higher knowledge: (1) genetic counselling, (2) higher social class, (3) child with NF1, (4) when NF1 had influenced reproductive decisions, (5) young age at diagnosis, and (6) member of a patient support group. The majority of the affected subjects perceived themselves to be more severely affected than by medical classification, with persons who had been diagnosed later in life, had a child with NF1, or who were concerned about the cosmetic aspects of the disease perceiving themselves to be more severely affected. Assessment of the psychosocial effects of NF1 at different stages of life showed that 63% of affected subjects experienced difficulties at school and 48% said that the condition, particularly cosmetic aspects, caused anxiety during adolescence (n = 54). These difficulties may have contributed to later problems with career attainment and confidence in relationships. Seventy-seven percent of parents stated that their child was experiencing difficulties at school relating to NF1 (n = 51). Of the subjects at risk of having a child with NF1 and who knew about NF1 before having their family (n = 32), 45% said that it had influenced their reproductive decisions. Of 29 subjects who were still considering children, 41% wished to have prenatal diagnosis in a future pregnancy, but only three subjects stated that they would terminate an affected pregnancy.